The Bracka two-stage repair for severe proximal hypospadias: A single center experience - Rakesh S Joshi; Mitesh K Bachani; Amit M Uttarwar; Jaishri I Ramji (Wolters Kluwer Medknow Publications, 2015)
Background: Surgical correction of severe proximal hypospadias represents a significant surgical challenge and single-stage corrections are often associated with complications and reoperations. Bracka two-stage repair is an attractive alternative surgical procedure with superior, reliable, and reproducible results. Purpose: To study the feasibility and applicability of Bracka two-stage repair for the severe proximal hypospadias and to analyze the outcomes and complications of this surgical technique. Materials and Methods: This prospective study was conducted from January 2011 to December 2013. Bracka two-stage repair was performed using inner preputial skin as a free graft in subjects with proximal hypospadias in whom severe degree of chordee and/or poor urethral plate was present. Only primary cases were included in this study. All subjects received three doses of intra-muscular testosterone 3 weeks apart before first stage. Second stage was performed 6 months after the first stage. Follow-up ranged from 6 months to 24 months. Results: A total of 43 patients operated for Bracka repair, out of which 30 patients completed two-stage repair. Mean age of the patients was 4 years and 8 months. We achieved 100% graft uptake and no revision was required. Three patients developed fistula, while two had metal stenosis. Glans dehiscence, urethral stricture and the residual chordee were not found during follow-up and satisfactory cosmetic results with good urinary stream were achieved in all cases. Conclusion: The Bracka two-stage repair is a safe and reliable approach in select patients in whom it is impractical to maintain the axial integrity of the urethral plate, and, therefore, a full circumference urethral reconstruction become necessary. This gives good results both in terms of restoration of normal function with minimal complication.